IMPLEMENTASI STANDAR PELAYANAN MINIMAL PADA MASA NEW NORMAL DI PUSKESMAS KASSI KASSI KOTA MAKASSAR - Nurarifah Khobsah, Farra Madinatun; Sudarmi, Sudarmi; Hawing, Hardianto (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of the study was to find out the implementation of minimum service standards during the new normal period at the Kassi-Kassi Public Health Center in Makaassar City. The research method used is qualitative. The results showed 1) Standards and policy targets including SOPs applied in the minimum service standards at Kassi Kassi Health Center Makassar City had been pegged and measured, besides that there was an increase in SPM achievements, 2) the resources at Kassi Kassi Public Health Center had met and were sufficient both from infrastructure and facilities such as TCM, complete medical equipment, elevators, 58 POSHBINDU, 3) Relationships between organizations are very supportive, such as BIN collaborating with the puskesmas for vaccination activities, in addition the government encourages direct innovation of digital services such as SOBAT TB, LSMILL , SITRUS, 4) the characteristics of implementing agents have understood their respective duties and responsibilities, 5) social, economic, political conditions are very supportive where visitors who perform services feel safe and comfortable and there is no discrimination in the services provided, 6) disposition of the agent implementor implementers are consistent and always evaluate the implementation of SPM and every year an evaluation is held for the progress of SPM.